When choice is not performative: the struggle for agency among women accessing family planning services in Senegal - Thais Gonzalez-Capella; Marieme Fall; Mbenoye Ndiaye; Cheikh Issa Diop; Manuela Reveiz; Nour Horanieh; Elizabeth Larson; Beniamino Cislaghi (Frontiers in Global Women's Health, 2026)
Introduction Despite ongoing efforts to improve family planning (FP) counselling as a means of increasing uptake and safeguarding women's sexual and reproductive rights, interactions between FP providers and users continue to play a decisive role in shaping contraceptive decisions. In practice, these encounters may influence method choice in ways that raise questions about the extent of women's reproductive autonomy. Drawing on theoretical perspectives on agency and informed choice, this study examines how women in Senegal navigate counselling and enact agency in FP decision-making. Methods This qualitative study included 256 participants (130 men and 126 women) from four Senegalese regions: Dakar, Tambacounda, Ziguinchor, and Matam. Data were collected through 116 semi-structured interviews and 16 focus group discussions (8–10 participants per group), using purposive sampling. Discussions explored experiences related to FP service delivery and data were analyzed thematically. Results Findings suggest that participants perceived some counselling practices as encouraging the adoption of LARCs in ways that limited their ability to make autonomous contraceptive decisions and influenced method choice during client-provider counselling interactions in Senegal. Women described a range of counselling practices from providers, such as presenting the implant as the primary or only available method, selectively emphasizing or omitting side-effects, limiting opportunities for dialogue, or expressing resistance to implant removal. In response to these dynamics, some women reported choosing to withdraw from contraception altogether. Such decisions may reflect constrained circumstances in which exercising agency may come at the expense of women's reproductive intentions and the right to effectively manage the timing and spacing of their own pregnancies. Discussion Safeguarding freedom of choice, and the ability to act upon that choice is a central but complex objective of FP programming in Francophone West Africa (FWA). Our findings underscore the pressing need for improved policy dialogue and ethical reflection on FP service delivery practices, more focused on women's lived experiences, including their expressions of hesitation, fear, resistance, or withdrawal, which are essential to understanding how agency is enacted in practice and to strengthening rights-based approaches to family planning across contexts. Conclusion Based on the experience from 256 adult women and men of reproductive age in Senegal, this study demonstrates that method choice unfolds within complex normative and institutional landscapes, where counselling practices can either enable or constrain women's reproductive agency, underscoring the urgent need to strengthen rights-based, autonomy-centered family planning approaches.